GONAD: A new method for germline genome editing in mice and rats. (5th October 2021) - Namba, Masumi; Kobayashi, Tomoe; Koyano, Takayuki; Kohno, Mayumi; Ohtsuka, Masato; Matsuyama, Makoto
Abstract: Recent advances in the CRISPR/Cas9 system have demonstrated it to be an efficient gene‐editing technology for various organisms. Laboratory mice and rats are widely used as common models of human diseases; however, the current standard method to create genome‐engineered animals is laborious and involves three major steps: isolation of zygotes from females, ex vivo micromanipulation of zygotes, and implantation into pseudopregnant females. To circumvent this, we recently developed a novel method named Genome‐editing via Oviductal Nucleic Acids Delivery (GONAD). This method does not require the ex vivo handling of embryos; instead, it can execute gene editing with just one step, via the delivery of a genome‐editing mixture into embryos in the oviduct, by electroporation. Here, we present a further improvement of GONAD that is easily applicable to both mice and rats. It is a rapid, low‐cost, and ethical approach fulfilling the 3R principles of animal experimentation: Reduction, Replacement, and Refinement. This method has been reconstructed and renamed as "improved GONAD ( i ‐GONAD)" for mice, and "rat improved GONAD (rGONAD)" for rats. Abstract : We present a further improvement of GONAD that is easily applicable to both mice and rats. It is a rapid, low‐cost, and ethical approach fulfilling the 3R principles of animal experimentation: Reduction, Replacement, and Refinement.